Carbon Tax Implementation in Banten's Coal Power Plant: IRIO Method - Fahrizal Taufiqqurrachman; Edy Suhartono; Hartiningsih Astuti; Sutrisno; Retno Muslinawati (Yayasan Pendidikan Islam Bustanul Ulum Mojokerto, 2026)
Facing global commitments to reduce greenhouse gas emissions while promoting a just energy transition, implementing carbon taxes in the coal-fired power generation sector becomes a strategic policy requiring in-depth analysis of its spatial and sectoral economic impacts, particularly in regions with high concentrations of coal-fired power plants like Banten. This research focuses on determining the impact of carbon tax implementation at the Banten Power Plant in 2025. This study uses a quantitative research method, utilizing data on the amount of carbon emissions produced multiplied by the carbon tax rate of Rp 30,000/ton CO2e. The resulting carbon tax revenue is then used as an exogenous shock in the D sector: Electricity and Gas in Banten Province, as shown in the Indonesian IRIO table, as well as labor and community income sourced from the Indonesian Central Bureau of Statistics. The analysis methods used include backward and forward linkages, the impact of shocks on sector (D) on 17 other sectors, and capturing the spatial spillover effect on output, income, and labor in 34 provinces. The research results show that in Banten, the greatest impact on output, income, and labor is in the same sector, namely (G) Wholesale and Retail Trade; Repair of Motor Vehicles and Motorcycles. The greatest aggregate impact on output, income, and labor is in South Sumatra Province, and the majority is still dominated by provinces on Java Island.